PjBL vs PBL Models in Higher Education: A Comparative Study Using Analysis of Covariance - Fadhilah Fadhilah; Muhammad Husin; Rian Fadia Raddhin (STKIP Singkawang, 2023)
A learning model is a form of process or way of presenting learning activities from beginning to end. This learning model serves as a means of communication in the classroom. This study aims to determine whether there are differences in the evaluation of pure learning outcomes by applying the Project-Based Learning (PjBL) and Problem Based Learning (PBL) learning models with the Pretest score as a controller. The number of subjects in this study was 42 mining engineering students in applied physics courses using the purposive sampling method. Data was collected by asking questions before being given treatment and after being given treatment. The data analysis technique used is the analysis of covariance (ANCOVA) in evaluating student learning outcomes. The findings indicate that there are significant differences in learning outcomes between the Project-Based Learning (PjBL) learning model and the Problem Based Learning (PBL) learning model by controlling the Pretest score. The significance of the PjBL learning model gives different and higher results compared to the PBL learning model. The application of the Project-Based Learning learning model provides many more meaningful and meaningful learning experiences for students in improving the evaluation of learning outcomes.